PENGALAMAN KOMUNIKASI GURU HOMESCHOOLING - Hakim, Aji Zul; Hafiar, Hanny; Puspitasari, Lilis (EDUTECH, 2017)
Homeschooling is an alternative education model for child who find it less suited to formal school. In the development of this model reap the pros and cons in the society. Various attemps were made by institutions and association to change the paradigm of society, on of them by optimizing the role of teacher. Research with phenomenological approach is sought to know the communications behavior of homeschooling teacher. Eight teacher from four homeschooling institutions are involved through some in-depth interviews. In addition, data collection is done through participant obersvation and study of literature. The result showed the meaning of homeschooling affected by their experience in teaching, which affects their act in the form of personal branding, including their communications behaviour in contributing to the socialization of homeschooling.Homeschooling merupakan model pendidikan alternative bagi anak yang merasa kurang cocok dengan sekolah formal. Dalam perkembangannya model pendidikan ini menuai pro dan kontra di masyarakat. Berbagai upaya dilakukan oleh lembaga dan asosiasi untuk merubah paradigma masyarakat, salah satunya dengan optimalisasi peran guru. Penelitian dengan pendekatan fenomenologis ini berupaya mengetahui perilaku komunikasi Guru Homeschooling. Delapan orang Guru Homeschooling dari empat lembaga di Kota Bandung dilibatkan melalui wawancara mendalam. Selain itu, pengumpulan data dilakukan melalui observasi partisipatif dan studi kepustakaan. Hasil penelitian menunjukan pemaknaan homeschooling oleh guru dipengaruhi pengalaman mereka selama mengajar, yang mempengaruhi tindak lanjut mereka dalam membentuk personal branding, termasuk perilaku komunikasi mereka dalam berkontribusi pada sosialisasi homeschooling.